Quantum dot–polymer composites based on nanoporous polypropylene films with different draw ratios. (September 2016) - Bobrovsky, Alexey; Shibaev, Valery; Abramchuk, Sergey; Elyashevitch, Galina; Samokhvalov, Pavel; Oleinikov, Vladimir; Mochalov, Konstantin
Graphical abstract: Highlights: Novel inorganic–organic hybrid composites based on nanoporous PP are prepared. Quantum dots (QDs) were used as a fluorescent inorganic component of composite. Composites possess low light scattering and high fluorescence intensity. An aggregation of QDs was analyzed using TEM and confocal fluorescence microscopy. Abstract: Hybrid composites of polymers with fluorescent nanoparticles are unique materials combining good mechanical properties of the host polymer matrices and luminescent properties of the embedded nanoparticles. Here, we report on the optical characterization of novel inorganic–organic hybrid composites based on nanoporous polypropylene (PP) as a polymer matrix and quantum dots (QDs) as a fluorescent inorganic component. The first type of the composite films is prepared by absorption of CdSe/ZnS QDs onto the porous structure of the PP films, followed by annealing at 170 °C, i.e., above the melting point of the PP. The second type of the composite films is obtained by filling of porous QD–PP composites with a nematic liquid crystalline (LC) mixture. Both types of composites are characterized by low light scattering, which makes it possible to study their optical properties by absorbance and fluorescence spectroscopies. TEM and confocal fluorescence microscopy have been used to analyze the aggregation of QDs in composites of different types. It has been shown that introduction of QDs into PP with a low draw ratio decreases the degree of alignment of LC molecules embedded into the pores of QD–PP composite films.